DETERMINANTS OF CONSUMER PURCHASE INTENTION TOWARD ESSENTIAL OIL-BASED PERFUMES: EVIDENCE FROM SUBANG REGENCY - Rohayati Suci Indrianingsih; Rahmi Rahmawati (Agripreneur : Jurnal Pertanian Agribisnis, 2026)
The trend of using natural products, including essential oil perfumes, is currently growing in society. However, essential oil perfume producers have not been able to optimize marketing strategies that can attract consumers. Despite this growth, empirical studies that explain consumer purchasing intention and its determining factors for essential oil-based perfumes at the regional level remain limited. This study aims to analyze consumer purchasing intention in essential oil perfumes and the factors that influence it. The study was conducted in Subang Regency from August to December 2025. The approach used was quantitative with a survey method. The sample size in this study was 100 and was determined by accidental sampling technique. The data analysis employed was quantitative descriptive analysis and multiple linear regression analysis. The results of the study indicate that consumer intention in essential oil perfumes is relatively high. Price perception and quality perception have a significant influence on purchasing intention simultaneously. While partially, only price perception has a significant influence on purchasing intention in essential oil perfumes. Scientifically, this study contributes to consumer behavior literature by identifying price perception as a more dominant determinant than quality perception in shaping purchasing intention for natural perfume products in emerging local markets. These findings provide practical implications for essential oil perfume producers in formulating pricing strategies and enchancing product quality.